Epidemiological Situation of Crimean-Congo Hemorrhagic Fever (CCHF) in the South of Russia in 2010 and Prognosis for the Year of 2011 - N. F. Vasilenko (Проблемы особо опасных инфекций, 2011)
Presented are the data on Crimean hemorrhagic fever epidemiological situation and morbidity in the South and North-Caucasian Federal Districts of the Russian Federation in 2010. Epizootic situation in the Stavropol region has been analyzed. The prognosis as regards CHF for the year of 2011 in the territory of the South and North-Caucasian Federal Districts is presented, based on epizootiological monitoring .